Use of resting state-functional magnetic resonance imaging to assess the utility of focused meditation in post-coronavirus disease cognitive dysfunction (Indian Journal of Case Reports, 2021)
Post-coronavirus disease (COVID-19) syndrome is a well-recognized entity in which cognitive brain dysfunction is the most common presentation. Diagnosis and management of such patients are challenging. We describe an important brain finding of post-COVID-19 syndrome on resting (rs)-functional magnetic resonance imaging by mapping the default mode network of the brain which becomes dysfunctional thus causing patient symptoms and its correction by the technique of focused meditation.